Ultrasonographic diagnosis of bilateral renal carcinoma in a dog - Kambala, Swetha; K. Jeyaraja; N. Pazhanivel; S. Kavitha; R. Ramprabhu (Indian Journal of Veterinary Medicine, 2024)
Ten-year-old male Labrador dog was presented with the history of anorexia, weight loss, haematuria for a period of five days. Abdominal ultrasonography revealed solitary mixed echogenicity mass at caudal pole of both kidneys. Urinalysis revealed proteinuria, and leucocytosis. It was confirmed as renal carcinoma through fine needle aspiration cytology.